Naturalism and Normativity: A Critical Examination of the Subject-Based Model of Reasons. - MILEVSKI, VOIN (Prolegomena: Journal of Philosophy, 2026)
This paper critically examines Marko Jurjako's naturalistic, subject-based theory of normative reasons. Grounded in the idea that reasons arise from evolutionarily shaped cognitive capacities that regulate behaviour, Jurjako aims to account for normativity without invoking robust realism. Four related concerns are highlighted: (1) explaining reasons via adaptive utility does not settle the open question argument; (2) the biological dual-function model leaves open how it captures the pragmatic and semantic variety of normative language; (3) the subject-based framework could clarify how it distinguishes correct from mistaken reasoning within an idealised perspective; and (4) the naturalistic account explains detection but not how this capacity meets standards of epistemic justification. Overall, while Jurjako's approach convincingly shows why we believe in reasons and how they function motivationally, it remains incomplete as an account of their evaluative force and linguistic complexity.